1997
DOI: 10.1007/s004210050304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indomethacin and polyunsaturated fatty acid diet on exercise-induced hypoxaemia in master athletes

Abstract: We have previously reported a reduction in exercise-induced hypoxaemia following polyunsaturated fatty acid supplementation (PUFA). Although this might have been explained by increases in membrane fluidity, a clear explanation could not be provided due to potentially confounding influences of series-2 prosta- glandin mediated effects resulting from PUFA. In this investigation, ten master athletes [mean age 48.1 (SEM 6) years, maximal oxygen uptake (VO2max) 3.39 (SEM 0.21) l x min(-1)] completed a maximal cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Specific functional characteristics of small and large airway function were not obtained in the present study such that this relationship cannot be verified. On the other hand, in our study, as in other previous reports of submaximal exercise GED (1,2,(15)(16)(17), the maximal exercise challenge consisted of a ramp protocol in which workload is increased every 1-2 min. In such rapid incremental protocols, the time at each exercise stage may be insufficient to allow for stability of ventilatory parameters.…”
Section: Discussionmentioning
confidence: 78%
“…Specific functional characteristics of small and large airway function were not obtained in the present study such that this relationship cannot be verified. On the other hand, in our study, as in other previous reports of submaximal exercise GED (1,2,(15)(16)(17), the maximal exercise challenge consisted of a ramp protocol in which workload is increased every 1-2 min. In such rapid incremental protocols, the time at each exercise stage may be insufficient to allow for stability of ventilatory parameters.…”
Section: Discussionmentioning
confidence: 78%
“…They observed a 27% decrease in filtration pressure, resulting in a 10% decrease in pulmonary arterial pressure. In master athletes, Aguilaniu et al (1,2) observed a decrease in EIH severity after a PUFA diet. Because a PUFA diet is known to improve RBC deformability, a potential contribution of blood parameters to EIH genesis cannot be excluded.…”
Section: Eihmentioning
confidence: 99%
“…Second, high blood viscosity or RBC rigidity causes higher mechanical stress on the blood-gas barrier and may result in membrane disruptions. Aguilaniu et al (1) showed that 6 wk of a polyunsaturated fatty acid (PUFA) diet led to an upward shift in Pa O 2 in master athletes. PUFA regimens are known to improve RBC deformability and to reduce blood viscosity (15); however, hemorheological measurements were not performed in this study (1).…”
mentioning
confidence: 99%
“…Several studies have suggested that changes in blood rheology may be involved in both pulmonary capillary damage and gas exchange impairment observed in exercising animals and humans [1,3,20]. RBCs are implicated since adequate blood flow in capillaries for pulmonary gas exchange is primarily dependent on their deformability.…”
Section: Introductionmentioning
confidence: 99%
“…EIH is defined as an inability to maintain an adequate level of oxygenation in arterial blood, leading to low partial pressure of oxygen and low hemoglobin saturation during intense exercise [8]. In master athletes with EIH, Aguilianu et al [1] observed an upward shift in partial pressure of oxygen in arterial blood after six weeks of daily oral supplementation with polyunsaturated fatty acid, a diet known to increase RBC deformability and to decrease hb [15]. Aguilianu et al [1] did not perform hemorheological measurements, and it is still unknown whether hb is higher or RBC deformability is lower in athletes with EIH.…”
Section: Introductionmentioning
confidence: 99%